The severity and atypical presentations of COVID-19 infection in pediatrics - Nagwan Y. Saleh; Hesham M. Aboelghar; Sherif S. Salem; Reda A. Ibrahem; Fatma O. Khalil; Ahmed S. Abdelgawad; Asmaa A. Mahmoud (BMC, 2021)
Abstract Background Emergence of 2019-nCoV attracted global attention and WHO declared COVID-19 a public health emergency of international concern. Therefore we aimed to explore the severity and atypical manifestations of COVID-19 among children. Methods This is an observational cohort study conducted on 398 children with confirmed COVID-19 by using real-time reverse transcriptase polymerase chain reaction assay for detection of 2019-nCoV nucleic acid during the period from March to November 2020. Patients were subdivided regarding the severity of COVID-19 presentation into Group I (Non-severe COVID-19) was admitted into wards and Group II (Severe COVID-19) admitted into the PICU. Results Non- severe cases were 295cases (74.1%) and 103cases (25.9%) of severe cases. There was a significant difference between age groups of the affected children (P < 0.001) with a median (0-15 years). Boys (52%) are more affected than girls (48%) with significant differences (P < 0.001). 68.6%of confirmed cases had contact history to family members infected with COVID-19. 41.7% of severe patients needed mechanical ventilation. Death of 20.4% of severe cases. In COVID-19 patients, fever, headache, fatigue and shock were the most prominent presentations (95, 60.3, 57.8, and 21.8% respectively). 3.5% of children were manifested with atypical presentations; 1.25% manifested by pictures of acute pancreatitis, 1.25% presented by manifestations of deep venous thrombosis and 1.0% had multisystem inflammatory syndrome (MIS-C). Multivariate regression analysis showed that COVID-19 severity in children was significantly higher among children with higher levels of D-dimer, hypoxia, shock and mechanical ventilation. Conclusion Most children had a non-severe type of COVID-19 and children with severe type had higher levels of D-dimer, hypoxia, shock and mechanical ventilation.